SPINT1-AS1 Drives Cervical Cancer Progression via Repressing miR-214 Biogenesis - Song, Hongjuan; Liu, Yuan; Liang, Hui; Jin, Xin; Liu, Liping (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidences have revealed the dysregulated expressions and critical roles of non-coding RNAs in various malignancies, including cervical cancer. Nevertheless, our knowledge about the vast majority of non-coding RNAs is still lacking. Here we identified long non-coding RNA (lncRNA) SPINT1-AS1 as a novel cervical cancer-associated lncRNA. SPINT1-AS1 was increased in cervical cancer and correlated with advanced stage and poor prognosis. SPINT1-AS1 was a direct downstream target of miR-214, a well-known tumor suppressive microRNA (miRNA) in cervical cancer. Intriguingly, SPINT1-AS1 was also found to repress miR-214 biogenesis via binding DNM3OS, the primary transcript of miR-214. The interaction between SPINT1-AS1 and DNM3OS repressed the binding of DROSHA and DGCR8 to DNM3OS, blocked DNM3OS cleavage, and therefore repressed mature miR-214 biogenesis. The expression of SPINT1-AS1 was significantly negatively correlated with miR-214 in cervical cancer tissues, supporting the reciprocal repression between SPINT1-AS1 and miR-214 in vivo. Through downregulating mature miR-214 level, SPINT1-AS1 upregulated the expression of β-catenin, a target of miR-214. Thus, SPINT1-AS1 further activated Wnt/β-catenin signaling in cervical cancer. Functionally, SPINT1-AS1 drove cervical cancer cellular proliferation, migration, and invasion in vitro, and also tumorigenesis in vivo. Deletion of the region mediating the interaction between SPINT1-AS1 and DNM3OS, overexpression of miR-214, and inhibition of Wnt/β-catenin signaling all reversed the roles of SPINT1-AS1 in cervical cancer. Collectively, these findings identified SPINT1-AS1 as a novel cervical cancer-associated oncogenic lncRNA which represses miR-214 biogenesis and activates Wnt/β-catenin signaling, highlighting its potential as prognostic biomarker and therapeutic target for cervical cancer.